European contract law in a changed banking and financial architecture : stability design, the common good, and private party participation / edited by Stefan Grundmann, Pietro Sirena. - Grundmann, Stefan, 1958-; Sirena, Pietro (European contract law and theory series ;, 2024)
The European Banking Union forms the answer of the EU to the global financial crisis, strongly increasing own funds basis for more robust credit institutions, installing a recovery and resolution regime with strong planning and preventive measures and opting for the supervisory with the broadest reach, the European Central Bank. The first part of the book - after the design of the overall architecture and a clarification of the main policy lines and theoretical underpinnings - describes the main features of this regime. It does so in particular for recovery tools and their conceptual novelty, focusing on private claims within the regime, namely within deposit guarantee schemes and for liability of supervisory authorities.